KEPUASAN KERJA MEMEDIASI PRODUKTIVITAS DOSEN DAN TENAGA KEPENDIDIKAN SAAT WORK FROM HOME (?) - Afni Sirait; Sri Luna Murdianingrum (METHOSIKA: Jurnal Akuntansi dan Keuangan Methodist, 2020)
The COVID-19 pandemic has brought many changes in various sectors. The education sector is one of the sectors that is significantly affected and must adapt as soon as possible to changes due to government regulations and policies. The purpose of this research is to analyze the productivity of lecturers and education personnel due to WFH policies and to mediate job satisfaction factors. The population of this study was lecturers and education staff in the FEB UPN "Veteran" Yogyakarta and a total sample of 85 respondents. Data were collected by distributing questionnaires, testing the validity, reliability, and testing the structural evaluation of the model data processing using SmartPLS. The results of the direct effect obtained the path coefficient value of 0.611 that the indirect effect was 0.386. This path coefficient value explains that there is a direct, positive, and significant relationship between endogenous and exogenous variables, but the mediating variable only has a partial effect. This research is expected to provide additional considerations for policymakers in the FEB UPN "Veteran" Yogyakarta in managing the productivity of lecturers and educational staff.